Kajian Tarif pada Perencanaan KRL-SRRL Fase 1 Berdasarkan Ability to Pay dan Willingness to Pay - Leliana, Arinda; Soimun, Ahmad; Apriliani, Nurul Fitria; Puspitasari, Armyta (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Surabaya and the Gerbang Kertasusila Metropolitan Area do not yet have a competent urban public transport system or regional public transport system. The government will introduce electric-based public rail transportation or known as KRL-SRRL in the Kertasusila Gate area. Construction of KRL-SRRL Phase 1 across Surabaya Pasar Turi-Sidoarjo, if operational, will overlap with the Local Train which is now operating. In future KRL-SRRL phase 1 operations, the operator must consider the purchasing power of prospective KRL-SRRL phase 1 users. This research aims to examine how affordable the purchasing power of prospective KRL-SRRL users is based on Ability to Pay (ATP) and Willingness to Pay (WTP) and knowing the relationship between ATP and WTP. The method used to determine the ATP value of potential KRL-SRRL service users is based on income and expenditure on transportation services used household budget method. The WTP value of potential KRL-SRRL service users is based on the average expected fare preference using the approach discrete choice analysis with model logit binominal. Overall, the average ATP for prospective KRL SRRL passengers with SBY-SDA relations is IDR 475,28/km. Meanwhile, the WTP for prospective KRL SRRL passengers with SBY-SDA relations is IDR 341,42/km. The fare that prospective KRL-SRRL passengers can afford is a maximum flat fare of IDR 13,000 for one trip from SBY-SDA. The relationship between ability to pay (ATP) and Willingness to pay (WTP) analysis results show that the ATP value is greater than the WTP value. This shows that prospective KRL SRRL passengers with SBY-SDA relations are choice riders.